Desenvolvimento de um sistema de inspeção de componentes utilizando técnicas de visão computacional - Prado, Wendel da Costa (2022)
This course conclusion paper (CCP) aims to present a system that, through Computer Vision, can identify the presence of electronic components on electronic boards, without human intervention, and make decisions by triggering a panel that displays the localized error. Thus, to develop a system that can capture data such as perimeter, part area, position, color, using only one sensor, and from these characteristics the system will be able to show if a specific component is missing or if it is showing some type of failure, such as: absence of a terminal or displacement.